Ground Wheat Grain for Midlactation Cows: Challenging a Common Wisdom - A. Nikkhah; F. Amiri; H. Amanloo (The Scientific World Journal)
The objective was to determine the effects of ground wheat grain (GW) inclusion rate, grinding extent (GE), and their interaction on lactating cow performance. Eight midlactation cows in 3×4 m individual boxes were used in a 4×4 replicated Latin square design study with 4 21 d periods. GW was fed at either 10% or 20% of diet dry matter (DM), as either finer or coarser particles. DM intake increased and net energy for lactation (NEL) intake tended to increase when GW was fed at 10% instead of 20% of diet DM. Milk energy yield, milk solids content and yield, and urine pH were unaffected. Fecal pH tended to increase at 20% versus 10% GW. Total tract apparent NDF, but not DM, digestibility tended to be greater for coarsely than finely GW and tended to be greater at 10% versus 20% GW. GW at 10% versus 20% of diet DM decreased blood BHBA and increased blood concentrations of total proteins and albumin. Data provide novel evidence that both finely and coarsely ground WG can be safely fed up to 20% midlactation cows. Commercial accessibility and cost will determine feeding preference of wheat grain to dairy cows.